Food consumption of Brumadinho Health Project participants - Mary Anne Nascimento-Souza; Patrícia Pinheiro de Freitas; Mariana Souza Lopes; Josélia Oliveira Araújo Firmo; Sérgio Viana Peixoto; Aline Cristine Souza Lopes (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT: Objective: To analyze the food consumption patterns of residents of Brumadinho, Minas Gerais, Brazil, according to sociodemographic characteristics, neighborhood and area of residence. Methods: Cross-sectional study with baseline data from the Brumadinho Health Project, conducted with 2,805 adult individuals. The healthy food consumption markers analyzed were: fruits and vegetables (FV), beans and fish; the unhealthy markers were: sweets and soda/artificial juices, whole-fat milk and red meat with visible fat or chicken with skin. Prevalence values and 95% confidence intervals were calculated for the total sample and according to sociodemographic characteristics, presence of commercial establishments with varieties of FV in the neighborhood and area of residence affected by the dam failure. Results: Among the healthy food consumption markers, the most common was beans (81.6%), and among the unhealthy ones, whole-fat milk (68.8%) and red meat with visible fat/chicken with skin (61.1%). Women were more prone to higher consumption of FV, while men, of beans and fish; the prevalence of these markers was higher among individuals with higher education degrees and higher incomes. Unhealthy eating markers were more prevalent among men, younger people, individuals with lower educational level and lower incomes, and residents in an area directly affected by the dam failure or in a mining region. Conclusion: Less than half of the participants were considered to follow regular or recommended consumption of healthy eating markers, except for beans. Individual characteristics and area of residence were associated with individuals' food consumption patterns and should be taken into account in actions to promote adequate and healthy eating.